Three-cycle fentanyl patch system contributes to stable control of plasma fentanyl concentration in gynecologic cancer pain patients - Chiharu Kanamori; Takanobu Kanamori; Yoshiaki Tanaka; Hideharu Kanzaki (Elsevier, 2011)
Objective: Pain affects many cancer patients in advancing stages, lowering the level of their quality of life. Morphine has long been the "gold standard" for the treatment of cancer pain; however, its side effects, particularly sedation and cognitive impairment at high doses, have encouraged the use of "opioid rotation". The transdermal fentanyl patch has advantages over oral morphine, with reduced side effects and increased convenience in practical usage. The side effects were reduced in patients who changed to the fentanyl patch, but rescue analgesia was often needed because of the decrease of fentanyl release from the patch, especially on patch replacement day. To maintain a stable fentanyl plasma level before patch replacement, we have established a three-cycle fentanyl patch system and reported that it provided appropriate pain control. The objective of this study was to investigate the individual variability of plasma fentanyl concentration in a three-cycle fentanyl patch system. Case Report: The gynecologic cancer patients were treated using the three-cycle fentanyl patch system. Blood samples were taken from the patients and plasma fentanyl concentration was analyzed. A stable plasma fentanyl level was observed, and good pain control was achieved in each patient using the three-cycle fentanyl patch system. A stable plasma fentanyl level was maintained the day before the conventional patch replacement day. Discussion: The three-cycle fentanyl patch system provided a stable plasma fentanyl concentration and excellent pain relief and should be considered for pain control in cancer patients.